"É como se fosse uma Olimpíada de verdade": sentidos construídos pelos atletas participantes dos Jogos Olímpicos da Juventude de Buenos Aires 2018 - Souza, Adriano Lopes de (2020)
Sport is a worldwide socio-cultural phenomenon, capable of representing the guiding thread of a set of relationships, interactions and valuations established between individuals at different times and contexts. The present notion that sport is an educatio